Updates to the Spectrum/Estimation and Projection Package (EPP) model to estimate HIV trends for adults and children. (20th November 2012) - Stover, John; Brown, Tim; Marston, Milly
Abstract : Background: The Spectrum and Estimation and Projection Package (EPP) programs are used to estimate key HIV indicators based on HIV surveillance and surveys, programme statistics and epidemic patterns. These indicators include the number of people living with HIV, new infections, AIDS deaths, AIDS orphans, the number of adults and children needing treatment, the need for preventing mother to child transmission (PMTCT) and the impact of antiretroviral treatment on survival. Methods: The Joint United Nations Programme on HIV and AIDS (UNAIDS) Reference Group on Estimates, Models and Projections regularly reviews new data and information needs and recommends updates to the methodology and assumptions used in Spectrum. The latest updates described here were used in the 2011 round of global estimates. Results: Spectrum and EPP have now been combined into one software package to enhance ease of use and ensure consistent data and assumptions for the curve fitting and indicator estimations. Major enhancements to the methods include a new adult model that tracks the HIV+ population by CD4 count; new patterns describing child survival by time of infection (perinatally, <6 months, 7–12 months and 12+ months after birth); a more detailed estimate of mother-to-child transmission that includes differential transmission rates by CD4 count of the mother, the effects of incident infections and new prophylaxis options; and new procedures to estimate uncertainty ranges around regional estimates. Conclusions: The revised model and software facilitate the preparation of new HIV estimates and use new data to address emerging needs for better information on need for treatment among adults and children.